Environmental Ethics in Surah Al-Baqarah verse 30 - Wiseno, Sekar Galuh Putri; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
Industrial society has an undesirable impact on environmental sustainability, namely environmental damage. Environmental damage demands serious action from all parties, including the government and those involved in the damage. One alternative way is with guidelines or regulations to all parties who violate. Environmental damage is not in harmony with religion teaching environmental sustainability in accordance with surah Al Baqarah verse 30. This research uses a qualitative approach with library research method. The subject of this study is surah Al-Baqarah verse 30 and the object of research is the thought and can be analyzed and applied in surah Al-Baqarah verse 30 which contains environmental ethics and freedom in the surrounding environment.